Direct comparison of F-l 8-FDG PET and ultrasound in the follow-up of patients with squamous cell cancer of the head and neck - Goerres, G. W.; Haenggeli, C. A.; Allaoua, M.; Albrecht, S. R.; Dulguerov, P.; Becker, M.; Allai, A. S.; Lehmann, W.; Slosman, D. O. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: The objective of this study was to compare screening ultrasound (US) obtained in patients with squamous cell carcinoma of the head and neck with F-l 8-FDG PET and to evaluate if US obtained before F-l 8-FDG PFT has the potential to enhance patient management by the detection of additional lesions. Method: 28 patients were prospectively included in the study (7 females and 21 males; range: 28-82 years). All had one follow-up examination after surgical treatment and/or radiotherapy using a combination of US and F-l 8-FDG PET on the same day (6-35 months after the end of treatment). Outcome was determined by either biopsyproven cancer recurrence or negative clinical follow-up for additional 6 months after this examination. Results: Regarding only the regions of the neck evaluated with both methods, US detected 25 suspect lesions vs. 9 lesions detected by F-l 8-FDG PET. Descriptive statistical analysis showed better sensitivity, specificity and accuracy of F-l 8-FDG PET. Only in 3 patients a lesion was detected in the same anatomical region using both methods. One patient was false positive with both methods. In another patient US detected a calcified right carotid artery plaque that lead to surgical therapy. Conclusion: F-l 8-FDG PET is better for the detection of clinically relevant lesions in the follow-up of patients with squamous cell carcinoma of the head and neck. In this study, the additional value of morphological information obtained by screening US performed before the PET scan is limited. US may not be a suitable test to improve interpretation of PET examinations.
Keywords: Positron emission tomography; sonography; head and neck cancer; follow-up examination; screening; ultrasound